Penerapan Metode Tutorial dalam Pembelajaran BTA di Pondok Pesantren Ath-Thohiriyyah Karangklesem Kidul Kecamatan Kedungbanteng Banyumas - Saefudin Ahmad (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: One of the subjects in the of Islamic education is BTA(Qur’anic Reading and Writing). Various methods have been used so that learners have competence in the field of BTA. One effective method is used in order to shape students to be competent in BTA is a tutorial method. This method has been applied in Pondon Pesantren Ath-Thohiriyyah, Karangsalam, Kedungbanteng, Banyumas. And the result, in less than half a year, almost all the students are able to read and write the Koran and memorize Juz 30. Keywords: Tutorial Method, Qur’anic Reading and Writing, Pondok Pesantren Ath-Thohiriyyah